A comparative study of reduced graphene oxide modified TiO2, ZnO and Ta2O5 in visible light photocatalytic/photochemical oxidation of methylene blue - Sun, Hongqi; Liu, Shizhen; Liu, Shaomin; Wang, Shaobin (elsevier, 2014)
Reduced graphene oxide (rGO) was applied to prepare various composites of rGO/photocatalyst of G/TiO2, G/ZnO and G/Ta2O5, using titanium (IV) isopropoxide, Zn powder and commercial Ta2O5 powder as photocatalyst precursors, respectively. X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), Fourier transform infrared spectroscopy (FTIR), thermogravimetric-differential thermal analysis (TG-DTA) and UV–vis diffuse reflectance (UV–vis DRS) were employed to investigate the crystal structure, morphology, surface groups, rGO loading, and optical properties of the produced composites. The photocatalytic activities of the composites under UV–vis and visible light were studied in degradation of methylene blue (MB). G/Ta2O5 showed an enhanced efficiency under UV–vis irradiation. G/TiO2 demonstrated an effective degradation of MB under visible light. The effects of various oxidants, peroxymonosulfate (PMS), peroxydisulfate (PDS) and hydrogen peroxide (H2O2) on MB degradation were thoroughly investigated. H2O2 was a promising oxidant for promoting MB degradation under visible light. The mechanism of the enhanced efficiency in the system of G/TiO2+ vis + H2O2 was discussed.